2008
DOI: 10.1016/j.ejcts.2008.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Tumor type M2-pyruvate-kinase levels in pleural fluid versus plasma in cancer patients: a further tool to define the need for invasive procedures☆

Abstract: Tumor M2-PK marker is useful in differentiating malignant from benign pleural effusions. Moreover, its sensitivity and NPV in pleural fluid are significantly higher compared to plasma. The usefulness of such a test is not strictly diagnostic but aims at excluding poorly performing patients from further invasive procedures. Thus, the inclusion of M2-PK within a panel of well-known tumor markers such as CEA, MCA, Ca 125 and Ca 19-9, may help in increasing the overall sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…In particular, PK-M2, a key enzyme in the glycolytic pathway, is overexpressed during multi-step carcinogenesis. This protein is found in blood, pleural effusion, stool, and other body fluids [17][18][19][20][21], and acts as a biomarker for esophagogastric, hepatopancreatobiliary, and colorectal malignancies [17].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PK-M2, a key enzyme in the glycolytic pathway, is overexpressed during multi-step carcinogenesis. This protein is found in blood, pleural effusion, stool, and other body fluids [17][18][19][20][21], and acts as a biomarker for esophagogastric, hepatopancreatobiliary, and colorectal malignancies [17].…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, M2‐PK is found to be mainly in the dimeric form and has therefore been termed “tumor M2‐PK.”5 Currently, the dimeric form can be detected by a specific antibody raised against it which does not react with the tetrameric form. M2‐PK can be detected in different body fluids, such as plasma, stool, and pleural fluid, and may have a role in the diagnosis of solid tumors including lung, ovary, cervix, breast, kidney, gastrointestinal tumors, and melanoma 6‐10. As yet, however, the role of M2‐PK in bile as a marker for BTC has not been investigated.…”
mentioning
confidence: 99%
“…Previous studies have shown that TuM2-PK can be detected in body uids, which may be due to the release of TuM2-PK during tumor necrosis or metastasis [19]. It has been reported that TuM2-PK was signi cantly increased in MPE, which can be used as an index to distinguish BPE and MPE [20]. The results showed that the levels of TuM2-PK in pleural effusion and serum of patients with MPE were signi cantly higher than those of patients with BPE, and increased most signi cantly in SCLC, which was signi cantly higher than those of lung ADC and SCC, while the levels of TuM2-PK in pleural effusion and serum of patients with ADC were also higher than those of patients with SCC, Therefore, TuM2-PK plays a certain role in the typing and diagnosis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%